Antioxidant and cytotoxic properties of two sea cucumbers, holothuria edulis lesson and stichopus horrens selenka - Althunibat, Osama Yousef; Hashim, Ridzwan; Bakhtiar, M. Taher; Daud, Jamaluddin; Arief Ichwan, Solachuddin Jauhari; Qaralleh, Haitham (Akadémiai Kiadó, 2013)
Sea cucumbers are marine invertebrates of the phylum of Echinodermata that have been used in Asian traditional medicine since ancient times. This study was conducted to investigate the antioxidant and cytotoxic properties of aqueous and organic extracts from two sea cucumber species, Holothuria edulis Lesson (Holothuriidae) and Stichopus horrens Selenka (Stichopodidae). Antioxidant activities of the extracts were used to demonstrate the cytotoxic effects of the extracts against two human cancer cell lines, non-small cell lung cancer cells (A549) and esophageal cancer cells (TE1). The results showed that both aqueous and organic extracts of H. edulis were able to scavenge DPPH radical (IC50 at 2.04 mg/ml and 8.73 mg/ml, respectively). Aqueous and organic extracts of S. horrens oxidation by linoleate free radical. On the other hand, the organic extract of S. horrens exhibited the highest cytotoxic effects against A549 and TE1 cancer cells giving IC50 at 15.5 and 4.0 μg/ml, respectively. In conclusion, the present study revealed that H. edulis and S. horrens contain promising levels of antioxidant